Performance enhancement and emissions reduction in a diesel engine using oleander and croton biodiesel doped with graphene nanoparticles - Treza Wambui Ng'ang'a; Meshack Hawi; Francis Njoka; joseph Ngugi Kamau (International Journal of Renewable Energy Development, 2023)
Petroleum diesel is non-renewable and a major contributor to environmental pollution and global warming. Biodiesel is a suitable substitute to diesel because it is renewable, environment-friendly and has a low carbon footprint. However, its high density, high viscosity and low heating value prevents it from replacing petroleum diesel completely. The current study seeks to establish the performance and emission characteristics of a compression ignition engine operating on Oleander and Croton biodiesel doped with graphene nanoparticles. Five fuel samples were used, including diesel (D100), diesel - 80% blended with Oleander and Croton biodiesel - 20% (OCB20) and OCB20 dosed with Graphene nanoparticles at mass fractions of 50 ppm (mg/L), 75 ppm (mg/L) and 100 ppm (mg/L), respectively. Engine tests revealed a significant improvement in brake thermal efficiency especially at 75 ppm concentration which was 2.76% % and 18.93% higher than diesel and OCB20, respectively and a reduction in brake specific fuel consumption by 2.44% and 16.67% compared to diesel and OCB20, respectively. Carbon monoxide (CO) and unburnt hydrocarbon emissions (UHC) decreased for the 50 ppm sample, recording 8.58% and 21.65% reduction in CO and 52.2% and 50% in UHC compared to the diesel and OCB20, respectively. However, NOx emissions increased. Graphene nanoparticle-enhanced biodiesel can therefore substitute petroleum diesel, albeit with NOx reduction techniques. Key words: Biodiesel; Compression ignition engine; Emission; Nano additives, Performance.